2016
DOI: 10.1002/chem.201504888
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic End‐Modulated Amino‐Acid‐Based Neutral Hydrogelators: Structure‐Specific Inclusion of Carbon Nanomaterials

Abstract: Hydrophobic end-modulated l-phenylalanine-containing triethylene glycol monomethyl ether tagged neutral hydrogelators (1-4) are developed. Investigations determine the gelators' structure-dependent inclusion of carbon nanomaterials (CNMs) in the self-assembled fibrillar network (SAFIN). The gelators (1, 3, and 4) can immobilize water and aqueous buffer (pH 3-7) with a minimum gelator concentration of 10-15 mg mL(-1). The hydrophobic parts of the gelators are varied from a long chain (C-16) to an extended aroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 74 publications
1
21
0
Order By: Relevance
“…The magnified aromatic region 1 H‐NMR spectra was given in Figure S8 that showed suppressed NMR‐signals of 2 in self‐assembled state compared to its non‐self‐assembled state. From the above data it can be assumed that a variety of intermolecular non‐covalent interactions (that were likely to be hydrogen bonding, hydrophobic interactions and others) between the amphiphiles are responsible during the self‐aggregation process . We further studied the molecular aggregation pattern within the vesicular morphologies.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The magnified aromatic region 1 H‐NMR spectra was given in Figure S8 that showed suppressed NMR‐signals of 2 in self‐assembled state compared to its non‐self‐assembled state. From the above data it can be assumed that a variety of intermolecular non‐covalent interactions (that were likely to be hydrogen bonding, hydrophobic interactions and others) between the amphiphiles are responsible during the self‐aggregation process . We further studied the molecular aggregation pattern within the vesicular morphologies.…”
Section: Resultsmentioning
confidence: 94%
“…To have a detailed insight into the various intermolecular non‐covalent interactions i. e. the driving forces acting within the self‐assemblies, we conducted FTIR, 1 H‐NMR, UV‐vis and fluorescence spectroscopy of 2 in self‐assembled and non‐self‐assembled condition both. FTIR spectra of 2 in non‐self‐assembled state (in DMSO‐D 6 ) showed sharp transmittance band at 1543, 1659 and ∼3373‐3413 cm −1 owing to amide δ N‐H (amide II, bending), ν C=O (amide I, stretching) and co‐existence of ν N‐H (amide A) with ν O‐H peaks, respectively (Figure a) . When 2 was taken in DMSO‐D 6 ‐D 2 O(1:400 v/v, in self‐assembled state), the transmittance signals were shifted to 1547, 1635 and ∼3360‐3452 cm −1 (broad band), respectively (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the FTIR spectra shown in Fig. 4, the main absorption bands were observed at υ = 3445/3288, 1650/1622, and 1544 cm −1 , which originated from υ N-H (amide A), amide υ C=O (amide I), and υ N-H (amide II) vibrations, respectively [25,26]. The band regions indicated that an H-bond was formed between the amide groups.…”
Section: Ft-ir Spectra Of Dbe Hydrogel Upon Uv Irradiationmentioning
confidence: 96%
“…Such dispersing approaches facilitate the bottom-up formation of highly ordered structures resulting in fascinating synergies, affording additional functions useful for a large number of applications ranging from sensing, catalysis, drug delivery and to tissue engineering. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] In this regard, the use of de novo peptides, whose sequence, length, structure and assembly can be conveniently tailored, is an efficient and elegant route for the preparation of stable CNT dispersions, [31][32][33][34][35][36] as well as for the directed incorporation of CNT building blocks into hierarchical structures 31,[37][38][39][40] and functional devices. [41][42][43] In particular, peptide-functionalized nanomaterials are increasingly playing an important role in tissue and biomedical engineering for the development of novel synthetic scaffolds for cell culture in vitro that closely resemble in vivo conditions and show improved biomimetic properties.…”
Section: Introductionmentioning
confidence: 99%